ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN TINGKAT HUNIAN D GAING MAS JIMBARAN VILLAS BALI: Fakultas Bisnis dan Pariwisata - Ibnu Habibi Fauzi; Luh Komang Candra Dewi (Journal Research of Management, 2023)
This study aims to find a suitable marketing strategy for Gaing Mas Jimbaran Villas Bali in increasing its occupancy rate, making it easier for the management of Gaing Mas Jimbaran Villas Bali to determine the next step in room marketing. This study uses the Qualitative Descriptive method. sampling in this study using Purposive Simpling techniques conducted by interviewing and distributing questionnaires to several respondents. The number of respondents in this study were 20 respondents which included 16 responses from the Management of Gaing Mas Jimbaran Villas Bali, 4 responses from guests\ The data analysis used is SWOT analysis. The result of this study is an IFAS value of 3.54 and an EFAS value of 3.89. Thus, Gaing Mas Jimbaran Villas Bali is in the fourth position I which is described as a growth position, so the right strategy is needed and the results are used to increase Gaing Mas Jimbaran Villas Bali room sales by strengthening market development. Marketing. Target audience and product development. From the results of this study it can be concluded that the need for the development of attractive strategic strategies such as, Strengthening Branding, maintaining Quality, more innovation in room marketing, and maintaining prices in accordance with the facilities offered.